2021
DOI: 10.3390/toxins14010002
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization and Functional Analysis of the Nattectin-like Toxin from the Venomous Fish Thalassophryne maculosa

Abstract: TmC4-47.2 is a toxin with myotoxic activity found in the venom of Thalassophryne maculosa, a venomous fish commonly found in Latin America whose envenomation produces an injury characterized by delayed neutrophil migration, production of major pro-inflammatory cytokines, and necrosis at the wound site, as well as a specific systemic immune response. However, there are few studies on the protein structure and functions associated with it. Here, the toxin was identified from the crude venom by chromatography and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 56 publications
(47 reference statements)
0
6
0
Order By: Relevance
“…Karatoxin 110kDa It is well known that fish venom is still largely unexplored as reported by (Silva et al, 2018;Xie et al, 2019;Gorman et al, 2020;Campos et al, 2021;Lopes-Ferreira et al, 2022) and in previous sections of this paper. Because there are few fish toxin sequences available as references, most of them are from Scorpaenidae and Synanceiidae families, it is challenging to research fish toxins and to create quick and effective techniques for wide exploration of toxin proteins or genes (Xie et al, 2017).…”
Section: Hypodytes Rubripinnis Nocitoxin 160kdamentioning
confidence: 66%
See 3 more Smart Citations
“…Karatoxin 110kDa It is well known that fish venom is still largely unexplored as reported by (Silva et al, 2018;Xie et al, 2019;Gorman et al, 2020;Campos et al, 2021;Lopes-Ferreira et al, 2022) and in previous sections of this paper. Because there are few fish toxin sequences available as references, most of them are from Scorpaenidae and Synanceiidae families, it is challenging to research fish toxins and to create quick and effective techniques for wide exploration of toxin proteins or genes (Xie et al, 2017).…”
Section: Hypodytes Rubripinnis Nocitoxin 160kdamentioning
confidence: 66%
“…Because there are few fish toxin sequences available as references, most of them are from Scorpaenidae and Synanceiidae families, it is challenging to research fish toxins and to create quick and effective techniques for wide exploration of toxin proteins or genes (Xie et al, 2017). Some recent studies have isolated and provided several toxins sequences using different techniques (Smith and Wheeler, 2006;Xie et al, 2016;Costa et al, 2018;Xie et al, 2019;Campos et al, 2021;Lopes-Ferreira et al, 2022), but due to a given number of venomous fish (>2000 species) (Saggiomo et al, 2021), it would be just a small portion of it.…”
Section: Hypodytes Rubripinnis Nocitoxin 160kdamentioning
confidence: 99%
See 2 more Smart Citations
“…The venom of snakes was approached in different aspects as the structural and functional variability in the composition of venoms from individual snakes [1], the mechanisms of action of whole venoms [2,3], the mechanisms of action of individual components as crotoxin [4], phospholipases A2 [5], metalloproteinases [6][7][8], and the oral immunity induced by whole venoms and their components [9]. Venoms from other animals are also reported; the venoms of centipedes [10], scorpions [11,12], fishes [13,14], and caterpillars [15], including microbial toxins [16]. The great potential for molecules derived from animal venoms as drug leads was also reviewed [17], and the antimicrobial [18], anticoagulant [19,20], and analgesic [21,22] effects have been highlighted in original studies reported here.…”
mentioning
confidence: 99%